Case Study: Correlations Between Curve Squeal, Weather Conditions, and Traction in a Tram Loop - Martin Valena; Milan Omasta; Milan Klapka; Radovan Galas; Vaclav Navratil; Ivan Krupka; Martin Hartl (Tribology in Industry)
This study explores the relationship between the coefficient of traction (CoT) and squeal noise parameters on a tram line loop, focusing on the influence of weather conditions. An automatic noise module was placed near a tram loop known for noise complaints. This module distinguishes between squeal and flange noise, recording their duration, root mean square (RMS) sound pressure level, and maximum sound pressure level when a threshold in the appropriate frequency band is exceeded. Concurrently, weather conditions were monitored, and the CoT on the rail was measured using a BUT rail tribometer. The findings reveal a notable correlation between the CoT and the duration of squeal noise, while the association with sound pressure levels was less pronounced. An increase in CoT was observed with rising relative humidity, which may be attributed to increasing temperature throughout a sunny April day, while absolute humidity remained almost constant. Furthermore, noise parameters rose with higher relative humidity and showed an inverse relationship with temperature. These findings suggest that weather conditions, particularly relative humidity and temperature, influence both the CoT and noise parameters on tram lines.